Clima laboral en el Comisariato del Libro del cantón Babahoyo periodo 2021. - Solano Bravo, Jimmy Josué (2022)
This case study determines the relationship between the work environment and the productive development of the employees or the book curatorship of the city of Babahoyo in the period May – September 2022. Whose objective is to analyze the work environment of the curator of the book, observe their work journey, how negative aspects affect employees such as por communication, not resolving conflicts in time and not staying fully motivated to fulfill their activities. The research that is carried out presents certain aspects that influence and does not allows to have a good working enviroment in this Company a descriptive type is used for wich a survey questionnaire was applied to the employees of the Company and the owner. The data that was processed through the investigation of the work environment of the Company. The concluisions were reached with the results of the research instrument applied to the case study, that the work environment is significantly related to the correct management of communication between leader and collaborator, conflicto resolution, teamwork and the interest in keeping workers motivated, wich i snot applied by the leader or the place, considering that they are relevant points that serve for employees to exercise their who come for the products offered by the commissary.